Dieulafoy’s Lesion of Ileum; Report of A Rare Case - Paikos, Dimitrios; Moschos, John; Sofianidis, Georgios; Zavos, Christos; Tikos, Georgios; Theodoridis, Konstantinos; Dimakopoulou, Aikaterini; Mpakas, Antonios; Raptis, Dimitrios; Papaziogas, Basilios (Archives of Clinical and Medical Case Reports, 2020)
Dieulafoy’s lesions (DLs) are dilated aberrant submucosal vessels, otherwise histologically normal, that erode the overlying epithelium in the absence of a primary ulcer, thereby causing a massive gastrointestinal (GI) bleeding. DLs are usually located in the proximal stomach along the lesser curvature, near the esophagogastric junction (typically within 5-6 cm). However, other locations throughout the GI tract have also been reported, such the esophagus, duodenum and colon. DL located in the ileum is extremely rare. Thus, we report a rare case of DL located 10 cm from the ileocecal valve, which treated endoscopically with hemoclips. On the fifth day post-endoscopic intervention, there were no signs of recurrent bleeding and the patient was discharged from our hospital. Most of the ileal DL cases reported in the literature were treated surgically. However, we believe that endoscopic treatment with thermal, mechanical (hemoclip or band ligation), or combination therapy (adrenaline injection combined with thermal or mechanical therapy) should be considered as the first-line management of bleeding DLs. Surgical resection should be reserved for: a. selected cases that cannot be treated with endoscopic or angiographic methods.